The quality assurance of teaching and learning in the Faculty of Business and Economic in University Pendidikan Sultan Idris - Ismail Khalid, Gadar Kamisan, Yeop Yunus Nek Kamal, (N/A, 2009)
The quality assurance of teaching and learning in the Faculty of Business and Economic in University Pendidikan Sultan Idris by Ismail Khalid, Gadar Kamisan, Yeop Yunus Nek Kamal,